Investigating Factors Influencing Mobile Money Service Adoption Among Small-Scale Entrepreneurs in Nigeria - Nathan Udoinyang (Journal of Social Entrepreneurship Theory and Practice, 2025)
The variables affecting acceptance of mobile banking services among small businesses in Nigeria are discussed in this research. Using a survey questionnaire to gather information from a sample of small-scale entrepreneurs in Nigeria, the study uses a mixed-methods research approach. The qualitative methodology was employed through the use of interviews. For small-scale entrepreneurs in Nigeria, the findings of the research reveal that age, education, income level, easy access and usefulness of mobile money service, security, low price of mobile money service, network availability, government backing, and financial knowledge are the factors influencing the use of mobile money service among small-scale entrepreneurs in Nigeria. While poor financial literacy, limited network availability in rural areas, restricted financial means, security and fraud, lack of mobile phone access, complexity of mobile money service, lack of trust, lack of understanding in the language used by mobile money services, cultural barriers, and inadequate knowledge about the use of mobile money services are the difficulties small-scale entrepreneurs face that affect their use of mobile money services Which is in support of Technology Acceptance Model (TAM) and Unified Theory of Acceptance and Use of Technology (UTAUT) that an individual's inclination to use a technology depends mostly on perceived usefulness (PU) and perceived ease of use (PEU). To encourage small-scale entrepreneurs in Nigeria to use mobile money services, the study suggests that mobile network operators, legislators, and other interested stakeholders should raise awareness and knowledge of them, enhance their perceived value and usability, and address security issues.